The influence of π-π-stacking on the light-harvesting properties of perylene bisimide antennas that are covalently linked to a [60]fullerene - Hofmann, Christiane C.; Lindner, Stefan M.; Ruppert, Michaela; Hirsch, Andreas; Haque, Saif A.; Thelakkat, Mukundan; Koehler, Juergen (Physical Chemistry Chemical Physics, 2010)
A flexible organic triad consisting of two perylene bisimide antennas covalently linked to a [60]fullerene by flexible spacers has been synthesized and studied by electrochemistry, steady-state and time-resolved spectroscopy. We found that π-π-stacking of the two antenna subunits has considerable impact on the photophysics of the system and leads to a reduction of the effective light-harvesting efficiency of the assembly. This finding is important for light harvesting in flexible materials based on the dye antenna-fullerene concept. © 2010 the Owner Societies.